Understanding COVID-19 preventive behavior: An application of the health belief model in the Philippine setting - Engracia Arceo; John Edlor Jurado; Leslee Anne Cortez; Nestor Sibug; Gestrelle Lides Sarmiento; Amica Coleen Lawingco; Carisse Carbungco; Raphael Enrique Tiongco (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: With the Philippines emerging as the hotspot in the Western Pacific Region for the COVID-19 cases, the study aimed to understand the COVID-19 preventive behavior of Filipinos using the health belief model (HBM). MATERIALS AND METHODS: The cross-sectional study included 304 respondents recruited for the whole month of July 2020 through various social media platforms. Participants were requested to answer an online questionnaire, and results were analyzed using SPSS software. RESULTS: The majority of respondents were female (71.1%), with an average age of 29, college graduate (57.6%), and living in an area where modified general community quarantine is implemented (63.2%). Good preventive behavior was noted among the participants, and not shaking of hands with others and refraining from touching of surfaces were reported as the most practiced behavior. Spearman's correlation and Pearson's Chi-square showed that age and sex are significant predictors for the HBM constructs and preventive behavior. Furthermore, results showed that cues to action, self-efficacy, and perceived barrier have a significant association with COVID-19 preventive behavior. CONCLUSION: Findings prove that HBM is useful in understanding preventive behaviors in times of coronavirus pandemic. Strategies that promote a supportive environment and help overcome the perceived barriers can guide Filipinos to adopt the desired health behavior. Interventions to promote preventive behaviors should be focused on males and younger individuals.